Optimal Organ Protection and Blood Pressure Control with the Single Pill Combination Lisinopril, Amlodipine and Indapamide in Arterial Hypertension - S. V. Nedogoda; T. N. Sanina; V. V. Tsoma; A. A. Ledyaeva; E. V. Chumachek; A. S. Salasyuk; D. S. Vlasov; O. I. Bychkova (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the single pill combination with lisinopril, amlodipine and indapamide ability in additional angioprotection achievement in patients with arterial hypertension and high pulse wave velocity (PWV) regardless on previous antihypertensive therapy (AHT).Material and methods. To the open non-randomized study duration 12 weeks 40 patients were included taking triple AHT during 6 months. All participants underwent ambulatory 24 hour blood pressure (BP) monitoring, applanation tonometry (augmentation index and central BP), pulse wave velocity assessment, laboratory tests (HbA1c, serum uric acid, high sensitive C-reactive protein [hsCRP], serum uric acid).Results. We observed additional systolic BP (SBP) and diastolic BP (DBP) reduction by 16.9% and 22.11% on lisinopril, amlodipine and indapamide single pill combination. Lisinopril, amlodipine and indapamide single pill combination decreased 24 h mean SBP by 16.77%, and 24 h mean DBP -23.5% (ABPM data), PWV by 19.7%, augmentation index by 14.81%, central SBP by 11.9% (p<0,05). There were positive changes in hsCRP level (-13.0%, p<0.05) and serum uric acid (-9.0%, p<0.05).Conclusion. Lisinopril, amlodipine and indapamide single pill combination provided control BP, arterial elastic properties improving (augmentation index, PWV, central BP) and favorable influence on inflammation and serum uric acid level.